Energy and emission analysis in the malaysian food industries - Ali, M.B.; Saidur, Rahman; Hasanuzzaman, M.; Ward, T.A. (Environmental Progress and Sustainable Energy, 2012)
According to the source paper written in 2006, the Malaysian food industrial sector accounted for about 14 of the total manufacturing energy consumption. As energy costs rapidly increase, alternative energy sources and efficiency improvements become essential to energy planning, cost savings, resource optimization, and environmental protection in these industries. This article focuses on the energy savings, economic benefits, and emission reduction that can be obtained by applying various energy saving options. This study shows that significant power can be saved annually by utilizing energy efficient motors. The cost savings, payback period, and reduction in CO 2 emissions are estimated for different motor loads. It is shown that sizeable amounts of energy can be saved using VSD, waste heat recovery, new efficiency lamps (T-5), and repairing leakages.